Innate immune signaling induces expression and shedding of the heparan sulfate proteoglycan syndecan‐4 in cardiac fibroblasts and myocytes, affecting inflammation in the pressure‐overloaded heart. (24th February 2013) - Strand, Mari E.; Herum, Kate M.; Rana, Zaheer A.; Skrbic, Biljana; Askevold, Erik T.; Dahl, Christen P.; Vistnes, Maria; Hasic, Almira; Kvaløy, Heidi; Sjaastad, Ivar; Carlson, Cathrine R.; Tønnessen, Theis; et al.
<x xml:space="preserve">Abstract</x> Sustained pressure overload induces heart failure, the main cause of mortality in the Western world. Increased understanding of the underlying molecular mechanisms is essential to improve heart failure treatment. Despite important functions in other tissues, cardiac proteoglycans have received little attention. Syndecan‐4, a transmembrane heparan sulfate proteoglycan, is essential for pathological remodeling, and we here investigated its expression and shedding during heart failure. Pressure overload induced by aortic banding for 24 h and 1 week in mice increased syndecan‐4 mRNA, which correlated with mRNA of inflammatory cytokines. In cardiac myocytes and fibroblasts, tumor necrosis factor‐α, interleukin‐1β and lipopolysaccharide through the toll‐like receptor‐4, induced syndecan‐4 mRNA. Bioinformatical and mutational analyses in HEK293 cells identified a functional site for the proinflammatory nuclear factor‐κB transcription factor in the syndecan‐4 promoter, and nuclear factor‐κB regulated syndecan‐4 mRNA in cardiac cells. Interestingly, tumor necrosis factor‐α, interleukin‐1β and lipopolysaccharide induced nuclear factor‐κB‐dependent shedding of the syndecan‐4 ectodomain from cardiac cells. Overexpression of syndecan‐4 with mutated enzyme‐interacting domains suggested enzyme‐dependent heparan sulfate chains to regulate shedding. In cardiac fibroblasts, lipopolysaccharide reduced focal adhesion assembly, shown by immunohistochemistry, suggesting that inflammation‐induced shedding affects function. After aortic banding, a time‐dependent cardiac recruitment of T lymphocytes was observed by measuring CD3, CD4 and CD8 mRNA, which was reduced in syndecan‐4 knockout hearts. Finally, syndecan‐4 mRNA and shedding were upregulated in failing human hearts. Conclusively, our data suggest that syndecan‐4 plays an important role in the immune response of the heart to increased pressure, influencing cardiac remodeling and failure progression.